Kinesiographic study of deglutition in dentate individuals and complete denture wearers - Sadalla, Karina Buainain de Freitas; de Souza, Raphael Freitas; Mollo, Francisco de Assis; Compagnoni, Marco Antonio [UNESP] (Chroma Inc, 2007)
Swallowing is used as a clinical method in prosthodontics to determine and record jaw relationships. The aim of this study was to perform a quantitative evaluation, in naturally dentate subjects and complete denture wearers, of three measurements associated with the mandibular position during the act of swallowing water: 1. intermaxillary distance on vertical axis; 2. anteroposterior deviation; and 3. lateral deviation. Two groups were selected: Group I (GI) included 40 subjects with complete dentition (mean age 45.27 yrs) and Group II (GII) included 40 bimaxillary edentate subjects, complete denture wearers (mean age 63.92 yrs). A kinesiographic instrument was used for analysis. Three records were taken for each measurement and a mean value obtained. It was concluded that: 1. intermaxillary distance on vertical axis and horizontal deviation were similar for both groups; 2. there was a significant intermaxillary distance on the vertical axis; and 3. for anteroposterior and lateral axis, results showed moderate deviation in relation to maximal intercuspation (MI).